2021
DOI: 10.1002/anie.202103540
|View full text |Cite
|
Sign up to set email alerts
|

Superfast and Water‐Insensitive Polymerization on α‐Amino Acid N‐Carboxyanhydrides to Prepare Polypeptides Using Tetraalkylammonium Carboxylate as the Initiator

Abstract: We design the tetraalkylammonium carboxylate‐initiated superfast polymerization on α‐amino acid N‐carboxyanhydrides (NCA) for efficient synthesis of polypeptides. Carboxylates, as a new class of initiator for NCA polymerization, can initiate the superfast NCA polymerization without the need of extra catalysts and the polymerization can be operated in open vessels at ambient condition without the use of glove box. Tetraalkylammonium carboxylate‐initiated polymerization on NCA easily affords block copolymers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 73 publications
0
38
0
Order By: Relevance
“…α-Helical polypeptides render excellent solubility in the polymerization medium to speed up the ROP process and exhibit “livingness” to make extended block copolymer architectures . α-Helical polypeptides such as poly­( l -lysine), poly­( l -glutamate), and so forth were reported using nickel- and cobalt-based organometallic catalysts, , Schreiner’s thiourea, N-heterocyclic carbenes (NHCs), fluorinated alcohol, crown-ethers, LiHMDS, and tetra-alkylammonium carboxylates and also methodologies like polymerization-induced self-assembly, , emulsion polymerization, , and so on. On the contrary, β-sheet polypeptides were known to undergo uncontrollable precipitation in polymerization medium, which further restricted the polymer chain growth and hampered the molecular-weight buildup .…”
Section: Introductionmentioning
confidence: 99%
“…α-Helical polypeptides render excellent solubility in the polymerization medium to speed up the ROP process and exhibit “livingness” to make extended block copolymer architectures . α-Helical polypeptides such as poly­( l -lysine), poly­( l -glutamate), and so forth were reported using nickel- and cobalt-based organometallic catalysts, , Schreiner’s thiourea, N-heterocyclic carbenes (NHCs), fluorinated alcohol, crown-ethers, LiHMDS, and tetra-alkylammonium carboxylates and also methodologies like polymerization-induced self-assembly, , emulsion polymerization, , and so on. On the contrary, β-sheet polypeptides were known to undergo uncontrollable precipitation in polymerization medium, which further restricted the polymer chain growth and hampered the molecular-weight buildup .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al recently published a method where NCA polymerization, initiated by a tetraalkylammonium carboxylate, is described to be faster than monomer hydrolysis (Scheme 2). 38 As a result, crude monomers can be used and solvents do not need to be dried prior to polymerization, which may significantly lower production costs.…”
Section: Water‐soluble Polymers In Home Carementioning
confidence: 99%
“…46 In contrast, the purification of water using chemical approaches is a more cost-effective method. The importance of chemical S C H E M E 1 Phosgene-free synthesis of NCA using diphenyl carbonate, reported by Koga et al 37 S C H E M E 2 Tetraalkylammonium carboxylate-initiated NCA polymerization, reported by Liu et al 38 S C H E M E 3 Structures of (A) disodium cis-epoxysuccinate and 2,3-oxiranernethane sulfonic acid sodium 39 and (B) polyether based on maleic anhydride and taurine 40 water treatment strategies is reflected in the global market size for water treatment chemicals, which was valued at USD 28.9 billion in 2019 and is expected to grow at a CAGR of 3.2% between 2020 and 2030. 47 Ground and surface water can be contaminated with dissolved substances and suspended or dispersed particles.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this method is generally used for the synthesis of polypeptides. 11 Furthermore, the copious carbon dioxide generated at the industrial level is a serious concern, particularly in a modern society that is striving toward carbon neutrality. In addition, the preparation of NCAs requires considerable skill because of the use of phosgene, an extremely poisonous chemical ( Scheme 1b ).…”
Section: Introductionmentioning
confidence: 99%